The best location selection using analytical hierarchy process method - Sulton Nur Hakim; Andika Julianto Putra (Universitas Ahmad Dahlan, 2022)
CHUUO Plain Shirt Factory is a plain shirt manufacturer founded in 2016 and is located at Kaliurang road Km 9, Yogyakarta. They not only sell plain t-shirts but also sell screen printing shirts, receive screen printing services, and orders to make collared shirts (polo). For CHUUO Plain Shirt Factory, business location has an important role in the marketing process related to reaching the customers. One method that can be used to determine the location of a new business is Analytical Hierarchy Process (AHP). This study focuses on selecting the best alternative location by considering seven criteria: geography, cost, population, risk, facilities & infrastructure, availability of human resources, and developer credibility. The research method used was observation and direct interviews using a questionnaire. The result shows that alternative location A (Shop at Gejayan Road No.30) has the highest all weight evaluation value (0.45). Alternative location B (Shop at Kaliurang Road Km 4) has a value of all weight evaluation of 0.3. Alternative location C (Shop at Magelang Road Km 7) has valued all weight evaluations the lowest (0.25). Based on the analytical research conducted, it can be concluded that alternative location A (Shop at Gejayan Road No.30) is the best location to open a branch shop for CHUUO Plain Shirt Factory.